Enhancing Pedagogical Competencies of Accounting Educators in Higher Education for the Digitalization Era - Denny Kurnia; Denny Putri Hapsari (International Journal of Management Research and Economics, 2025)
The rapid advancement of digitalization in the accounting field demands significant changes in the education process, particularly regarding the pedagogical competence of accounting educators. Pedagogical competence, which includes teaching skills relevant to modern technology, is crucial for preparing students to face challenges in the digital era. This study aims to analyze the development of pedagogical competence among accounting educators in higher education to address the challenges of accounting digitalization. The study was conducted using a qualitative descriptive method, with primary data collected from interviews and observations, as well as an in-depth literature review. The results indicate that integrating technology into accounting education requires enhancing the ability to use information and communication technology (ICT), in addition to adopting problem-solving-based teaching methods. Support from higher education institutions, particularly in the form of technology training, is a key factor in improving the pedagogical competence of accounting educators.